"They Didn't Talk About Stuff like That": Sexual Health Education Experiences of a Native American Tribe in the Gulf Coast. Issue 2 (3rd April 2023) - Liddell, Jessica L.; Herzberg, Juliet
Abstract: Native American groups in the United States experience extensive sexual and reproductive health disparities. However, the sexual health education and communication experiences of Native American groups are understudied. Thirty-one interviews were conducted with Native American women in the United States' Gulf Coast about their sexual and reproductive health experiences. Women reported the following themes: (a) Lack of Formal Sex Education; (b) Young Pregnancy; (c) Lack of Knowledge about HIV/STDs; (d) Lack of Communication about Menstruation; (e) Communication Experiences about Sexual and Reproductive Health; and (f) Stigma Around Discussing Sexual and Reproductive Topics. The findings of this research indicate that there are gaps in sexual health education and highlight the ways female tribal members act as health leaders in their communities.